2008
DOI: 10.1158/0008-5472.can-08-0859
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Mesenchymal Stem Cells Expressing PAX-FKHR Form Alveolar Rhabdomyosarcomas by Cooperating with Secondary Mutations

Abstract: Alveolar rhabdomyosarcomas (ARMS) are highly malignant soft-tissue sarcomas that arise in children, adolescents, and young adults. Although formation and expression of the PAX-FKHR fusion genes is thought to be the initiating event in this cancer, the role of PAX-FKHR in the neoplastic process remains largely unknown in a progenitor cell that is undefined. We hypothesize that PAX-FKHR determine the ARMS progenitor to the skeletal muscle lineage, which when coupled to the inactivation and/or activation of criti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 42 publications
4
88
0
Order By: Relevance
“…Additional expression of the constitutively active H-RAS G12V leads to tumor formation in all of the PAX-FKHR-expressing populations. These PAX-FKHRexpressing tumors display histological features and gene expression profiles similar to human ARMS [74].…”
Section: Arms Modelsmentioning
confidence: 85%
See 2 more Smart Citations
“…Additional expression of the constitutively active H-RAS G12V leads to tumor formation in all of the PAX-FKHR-expressing populations. These PAX-FKHRexpressing tumors display histological features and gene expression profiles similar to human ARMS [74].…”
Section: Arms Modelsmentioning
confidence: 85%
“…However, PAX3-FKHR and PAX7-FKHR fusions induced skeletal myogenesis but not transformation when introduced in BM-mMSCs [74]. Nevertheless, the expression of a dominant-negative form of p53 or SV40 large T antigen (which inactivates both p53 and Rb) elicits tumor formation in a proportion of the PAX-FKHR-expressing cells.…”
Section: Arms Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that BM-mMSCs provided a permissive environment for tumoral transformation and sarcoma development mediated by several sarcoma-associated fusion genes [2][3][4][5]. Nevertheless, a human sarcoma model remains to be developed.…”
Section: Discussionmentioning
confidence: 99%
“…Several types of sarcomas have been reproduced in vivo on overexpression of specific fusion oncoproteins in bone marrow (BM)-derived mouse MSCs (mMSCs). These models include the recapitulation of Ewing's sarcoma by expression in BM-mMSCs of EWS-FLI-1 [2,3], mixoid liposarcoma (MLS) by expression of FUS (FUsed in Sarcoma; also termed TLS, Translocated in LipoSarcoma)-CHOP (C/EBP HOmologous Protein; also termed DDIT3, DNA Damage-Inducible Transcript 3) [4], and alveolar rhabdomyosarcoma by expression of PAX-FKHR [5]. Furthermore, cancer-initiating cells displaying MSC properties have been recently identified in Ewing's Sarcoma [6].…”
Section: Introductionmentioning
confidence: 99%